Mubadalah as an Islamic Moderating Perspective between Gender and Patriarchal Regimes in Building Family Resilience - Septi Gumiandari; Ilman Nafi'a (LPPM UIN K.H. Abdurrahman Wahid Pekalongan, 2020)
The COVID-19 pandemic has a multidimensional impact, including threatening family resilience. Psychological pressure, as well as an increase in the burden of household domestic work due to concentrated activities (work, school) at home, can give rise to family conflicts that lead to domestic violence and divorce. This study aims to offer a Mubadalah concept as a perspective and methodology in building family resilience. The results show that (1) Mubadalah is a perspective of reciprocity between men and women in carrying out their gender roles both in the domestic and public area so that one does not hegemonize over another but a relationship that supports, cooperates, and helps each other; (2) Mubadalah can be a method of reading texts and contexts around family issues; and (3) Mubadalah is an Islamic moderating perspective between gender and patriarchal regimes. This perspective allows for a balanced relationship and partnership between the two sexes and is not just a transformation of thoughts from patriarchy to matriarchy. Through approach a companionship and non-hierarchical relationship between family members, family resilience can be built.